Intracranial Epidural Abscess In A 48-Years-Old Patient With Hystorical Uncontrolled Diabetes Melitus And Post Procedural Craniotomy For Intracerebral Hemorrhage : A Case Report - Faizin, Achmad Nur; Jani, Januardi Rifian (Riviera Publishing, 2025)
Intracranial epidural abscess (IEA) is a severe complication that can arise following skull surgery or as a result of trauma. It may also develop from infections related to otorhinolaryngological procedures or from issues involving the neck and thorax. The primary culprits behind these infections are often staphylococci, particularly Staphylococcus aureus, as well as various gram-negative bacteria. Patients typically present with a range of clinical symptoms, including fever, pain, headache, lethargy, nausea, vomiting, and photophobia. These symptoms may be accompanied by signs such as papilledema, sinus drainage, cranial nerve paralysis, and focal neurological deficits. In this case, we discuss a 48-year-old patient with poorly controlled diabetes mellitus who developed swelling following a cranioplasty. The patient reported fluctuating swelling in the head, headache, and fever one week after the operation. The study utilized a combination of observational methods, clinical evaluations, and analytical laboratory techniques, including the use of an aspiration needle to investigate the nature of the swelling. Aspiration revealed the presence of pus and blood, and further histopathological examination and culture confirmed an infection caused by Methicillin-Resistant Staphylococcus Aureus (MRSA). The patient subsequently underwent a repeat craniotomy to evacuate the abscess, followed by targeted antibiotic therapy. Over two weeks post-operatively, the patient experienced ongoing fluctuations in swelling and associated complaints, ultimately leading to a loss of smell. This case underscores the critical need for urgent attention to IEA, especially in patients with uncontrolled comorbidities like diabetes mellitus. Effective and timely management, which includes surgical intervention and culture-specific antibiotic therapy.